Sincere behaviour: Moderating leadership, culture and lecture performance in higher education - Fullchis Nurtjahjani; Forbis Ahamed; Ayu F. Puspita; Kadek S. Batubulan; Ane F. Novitasari (SA Journal of Human Resource Management)
Orientation: Higher education institutions have the potential to produce quality human resources. For this reason, it is necessary to monitor the quality of its teaching workforce.